Cursos de Letras no centro da arena discursiva da reforma curricular de uma universidade pública mato-grossense - Nunes, Jozanes Assunção (2017)
This paper aims to understand the complexity of the reform process of the Letters Course in the academic sphere, from the establishment of dialogic relations between the discourses of teachers who integrate the Structuring Teaching Core of the Letters courses of a public university in Mato Grosso and official discourses of education that deal with curricular restructuring of undergraduate courses. The worrying data about the last researches on the Letters course, released by official organs of the Ministry of Education, the approval of the CONAES n. 1/2010 Resolution, which rules the Structuring Teaching Core (NDE) in the scope of undergraduate courses, as well as the impasses and advances that we face in our trajectory as a professor and coordinator of a Letters Course were some of the reasons that led us to this study. The research was based on the theoretical-epidemiological and methodological assumption of Bakhtin and the Circle, which enabled us to understand the utterances of the research subjects in their discursive dimensions, favoring the debate around the reflections and reassessments of the principles and guidance of legal discourses related to courses restructuring. The research problem positions itself in the following question: How do professors who integrate the Structuring Teaching Core (NDE) of the Letters Courses being assessed by MEC respond, in their utterances, to the official discourses that deal with the curricular restructuring of undergraduate courses in Letters? In order to find the answers to the question, we established the research corpus through data collection carried out in two spheres of knowledge production: State (legality discourse, which deals with the restructuring of Letters and teacher training course) and university (discourse of the professors who integrate the NDE researched – subjects of the research). The data of the first sphere comprise: a) documents of the National Commission for the Evaluation of Higher Education (CONAES) that deal with the Structuring Teaching Core in the scope of undergraduate courses; b) Reports drawn up by the National Education Council (CNE) which underlie the Curriculum Guidelines, issued in 2001 and 2015, focused on Letters Courses and teacher’s training. The data of the second sphere comprise: a) those generated by means of a questionnaire answered by NDE members; b) Pedagogical Project of the Portuguese Language and Literature Letters Course, restructured by the research subjects; c) information obtained through a focus group interview provided by the same subjects. The study is based on the assumption that the statements produced by the NDE teachers, related to the restructuring of the Letters Course, tensely dialogue with the official voices that deal with the creation of NDE and with those that regulate and guide the teacher training courses. In this process, the official voices work in search of stability and centralization, seeking to homogenize the curricular reforms in the courses, while other voices act to erode this centralizing tendency, presenting different positions. From this perspective, we first analyzed the official statements of education and, later on, analyzed the statements produced by the NDE teachers. We defend that there is a clash of political-ideological forces that permeate the statements of the research subjects, provoking the most diverse responses to legal discourses. In general, the study of such statements indicates that: (1) the subjects of the research partially accepted the determinations of the official voices that guide the NDE in the scope of undergraduate courses, seeking, in union with their peers, a different form of constitution of the nucleus and development of the work; (2) the curricular proposals elaborated have their own character, producing different meanings from those of the Guidelines, regarding the organizing principles of the curriculum (flexibility, competence, theory and practice integration and interdisciplinarity), showing a dialogical relationship with the official discourse sometimes of acceptance, reiteration, others of refusal, complementation and re-enactment, and (3) the process of reforming the courses took place in an area of resistance